Competitiveness of the China-Europe Railway Express and liner shipping under the enforced sulfur emission control convention. (March 2020) - Lian, Feng; He, Yunzhu; Yang, Zhongzhen
Highlights: The liner shipping and China-Europe Railway express between China and Europe are targeted. The enforced sulfur emission convention of the IMO is taken as the background. The added cost of liner shipping companies due to the adoption of the measures is estimated. Transported commodities between China and Europe are clustered into 9 groups. The effects of the enforced sulfur emission convention on the sulfur and CO2 emissions in China-Europe freight market are forecasted. Abstract: The sensitivity of the pass-through ratio of the added costs due to the enforced sulfur emission cap of liner shipping as extra fare for shippers and rail operation frequency on the competitiveness of China-Europe railway express (CER-express) and liner shipping for cargo transportation between China and Europe is analyzed. The objective is to lay a theoretical basis for liner companies to optimize the pass-through ratio for maximizing shipping profit, for CER-express to determine an expected operation frequency and for IMO to understand the effects of the enforced sulfur emission cap when CER-express is available.